Hard tasks in the communication practice of multicultural organizations - Borgulya, Ágnes (Studia Mundi – Economica, 2015)
In organizations people very often have to fulfill tasks causing considerable stress. One such task is negotiating major decisions with possible harmful consequences. Decision-making can cause stress overload even in a mot cultural environment using one’s own mother tongue. If decisions have to be made under multicultural conditions, stress levels may increase even further because the social-psychological problems involved in cross-cultural interactions, linguistic differences and the different decision making styles of the participants act simultaneously. As medical research shows, an excessive degree of stress will hinder or even block communication.